Crystallization and preliminary X-ray diffraction analysis of three recombinant mutants of Vaccinia virus uracil DNA glycosylase - Sartmatova, Darika (International Union of Crystallography, 2013)
Amino-acid residues located at a highly flexible area in the uracil DNA glycosylase of Vaccinia virus were mutated. In the crystal structure of wild-type D4 these residues lie at the dimer interface. Specifically, three mutants were generated: (i) residue Arg167 was replaced with an alanine (R167AD4), (ii) residues Glu171, Ser172 and Pro173 were substituted with three glycine residues (3GD4) and (iii) residues Glu171 and Ser172 were deleted (Δ171-172D4). Mutant proteins were expressed, purified and crystallized in order to investigate the effects of these mutations on the structure of the protein.